2012
DOI: 10.1177/0269881112464827
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled pilot study of MDMA (±3,4-Methylenedioxymethamphetamine)-assisted psychotherapy for treatment of resistant, chronic Post-Traumatic Stress Disorder (PTSD)

Abstract: Psychiatrists and psychotherapists in the US (1970s to 1985 and Switzerland (1988Switzerland ( -1993 used MDMA legally as a prescription drug, to enhance the effectiveness of psychotherapy. Early reports suggest that it is useful in treating trauma-related disorders. Recently, the first completed pilot study of MDMA-assisted psychotherapy for PTSD yielded encouraging results. Designed to test the safety and efficacy of MDMA-assisted psychotherapy in patients with treatment-resistant PTSD; our randomized, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
334
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(350 citation statements)
references
References 46 publications
10
334
0
6
Order By: Relevance
“…Furthermore, propranolol-another pharmacological agent investigated as an adjunct for PTSD therapy (Brunet et al, 2008, but see Wood et al, 2015;Steenen et al, 2016)-decreases connectivity within the salience network (Hermans et al, 2011). Thus, it is worth considering whether action at the salience network might be an important component of the mechanism by which MDMA operates in MDMA-assisted psychotherapy for PTSD (Mithoefer et al, 2011;Mithoefer et al, 2012;Oehen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, propranolol-another pharmacological agent investigated as an adjunct for PTSD therapy (Brunet et al, 2008, but see Wood et al, 2015;Steenen et al, 2016)-decreases connectivity within the salience network (Hermans et al, 2011). Thus, it is worth considering whether action at the salience network might be an important component of the mechanism by which MDMA operates in MDMA-assisted psychotherapy for PTSD (Mithoefer et al, 2011;Mithoefer et al, 2012;Oehen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The first randomized controlled trials (RCTs) of MDMAassisted psychotherapy for treatment-resistant PTSD demonstrated decreases in both clinician-and participant-rated symptom severity (Mithoefer et al, 2011;Oehen et al, 2013). The efficacy of these interventions persisted at follow-up (Mithoefer et al, 2012), and effect sizes surpassed even those demonstrated by prolonged exposure therapy, the most widely accepted treatment for PTSD (Amoroso and Workman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] We will focus on two classes of psychedelics: classic psychedelics and "entactogens. "…”
Section: Types Of Psychedelic Drugsmentioning
confidence: 99%
“…The participants were randomly assigned to either the treatment group (receiving 200 µg LSD [n = 8]) or the active control group (20 µg LSD [n = 4], with an open-label crossover to 200 µg LSD after the initial blinding was unmasked). At two months' follow-up, the State-Trait Anxiety Inventory (STAI) showed nonsignificant reductions in [16][17][18] Note: DMT = dimethyltryptamine, LSD = lysergic acid diethylamide, MDMA = methylenedioxymethamphetamine, PTSD = posttraumatic stress disorder. *Potential harms identified here are associated with illicit and unsupervised nonmedical uses of psychedelic substances (often in the context of polysubstance use); current clinical studies on psychedelic agents have not reported such chronic adverse sequelae.…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation